Research Progress and Perspectives on the Influence of Flow Field Characteristics and Fish Interactions in Factory Recirculating Aquaculture Systems - Xiaozhong REN; Haibo LIU; Ying LIU; Yinxin ZHOU; Zonglong CHE; Meng LI (Progress in Fishery Sciences, 2023)
Both population and economic development are driving the rapid adoption of aquaculture development worldwide. The unique attributes of the intensive factory recirculating aquaculture system, including high density, low pollution, and high efficiency, have made this system an important avenue for aquaculture transformation and improvement, and this fits the current concept of green development in aquaculture. Flow patterns are an important environmental factor in the recirculating water aquaculture systems, with this parameter directly affecting the growth and welfare of fish within the system. However, it is also worth noting that the presence and movement of the fish also affect the construction of the system flow pattern. This study presents a comprehensive analysis of the effects of flow field conditions in recirculating aquaculture systems on different fish species, including the effects of flow rate on the growth and development, physiological indicators, and survival rates of commonly cultured fish, as well as the effects of other hydrodynamic conditions, such as circulating water and circulating water exchange rates, on fish behavior. The effects of fish and their locomotor behavior on hydrodynamic conditions and performance in culture ponds are also discussed, including the effects on turbulence intensity, flow-field flow patterns, and water mixing in these systems. The methods used to study the effect of fish movement on the flow field characteristics of any system can be broadly categorized into real measurement methods and numerical studies, where the real measurement methods include the visualization of research objects using the particle image velocimetry (PIV), acoustic Doppler velocimetry (ADV), and rhodamine water tracer fluorescence method. In contrast, numerical studies primarily rely on the application of the computational fluid dynamics (CFD) method. The advantages and disadvantages of both approaches are evaluated in this study. Our evaluations include a discussion of the common problems with the current system for constructing the circulating water aquaculture systems in industry, such as neglecting the flow field construction, lack of cross-disciplinary research, poor regularity, and repeatability of research, and suggest that a systematic experimental program should be established in combination with refined numerical simulation methods to facilitate the development of more accurate complex models. The aim of this study was to clarify the design of hydrodynamic conditions in these aquaculture systems in order to promote the development of better circulating water aquaculture systems for the industry in the hope of improving both the fish and water balance.